Survey for legume and cereal viruses in Iraq - El-Muadhidi, Muthana A.; Jerjess, Myasser; Makkouk, Safaa G.; Murad, Salou (Phytopathologia Mediterranea, 2001)
A survey was conducted in April 2000 to identify virus diseases affecting legume (chickpea, faba bean and lentil) and cereal (wheat and barley) crops at different locations in Iraq (Baghdad, Al-Anbar, Diyala, At-Tamim and Ninawa governorates). The survey covered 54 randomly selected legume fields (36 faba bean, 8 chickpea, and 10 lentil) and 23 cereal fields (18 wheat and 5 barley). All viruses were identified and their incidence determined by laboratory testing 100–200 randomly collected samples and 20–25 symptomatic samples from each field. A total of 7663 legume and 3455 cereal samples was collected and tested for 12 legume and 5 cereal viruses by tissue blot immunoassay (TBIA). In faba bean fields, Bean yellow mosaic virus (BYMV, genus Potyvirus, family Potyviridae) was the most common, followed by Bean leaf roll virus (BLRV, family Luteoviridae). In the 18 most extensively infected faba bean fields (more than 50%), total virus incidence ranged from 80 to 100%, and BYMV was by far the most common. Other viruses that were detected in legumes at low incidence were: Alfalfa mosaic virus (AlMV, genus Alfamovirus, family Bromoviridae), Faba bean necrotic yellows virus (FBNYV, genus Nanovirus), Cucumber mosaic virus (CMV, genus Cucumovirus, family Bromoviridae), Broad bean wilt virus (BBWV, genus Fabavirus, family Comoviridae), Beet western yellows virus (BWYV, genus Polerovirus, family Luteoviridae) and Chickpea chlorotic dwarf virus (CpCDV, genus Mastervirus, family Geminiviridae). This is the first report of FBNYV, BWYV and CpCDV infecting legumes in Iraq. In the cereal fields, Barley yellow dwarf virus-PAV (BYDV-PAV, genus Luteovirus, family Luteoviridae) was detected in about 1% of random samples. Virus disease incidence in all cereal fields based on field observations was less than 5%. Other viruses were rarely detected in cereals: BYDV-MAV (genus Luteovirus, family Luteoviridae) and Cereal yellow dwarf virus-RPV (CYDV-RPV, genus Polerovirus, family Luteoviridae).